Ritualitas ke Relasionalitas: Doa Pagi sebagai Strategi Pembinaan Rohani Siswa SMA Berbasis Nilai Galatia 5:22–23 - Edward Nimits Abraham (Sekolah Tinggi Teologia Kerusso Indonesia, 2025)
This study examines the impact of morningprayer on the spiritual growth of students at SMA Mahanaim Bekasi, focusing on cognitive, affective, and cognitive dimensions. Using a qualitative case study approach, data were collected through participatory observation, in-depth interviews, and documentation involving 15 students and supporting informants. The findings reveal that morning prayer significantly enhances students' understanding of biblical values (cognitive), deepens their spiritual awareness (affective), and fosters behavioral changes such as self-control and empathy (cognitive), aligning with the fruits of the Spirit in Galatians 5:22-23. Challenges include formalistic participation and monotonous implementation, which may diminish transformative effects. Strategic recommendations include contextual devotional modules, active student involvement, and periodic evaluations. The study underscores morning prayer as a transformative spiritual discipline, contributing to holistic Christian character education in an era of globalization.